Bangladesh Social Protection and Labor Review : Towards Smart Social Protection and Jobs for the Poor - World Bank (World Bank, Dhaka, Bangladesh, 2016)
Over the past decade, Bangladesh has achieved strong economic growth and impressive poverty reduction. The country’s great strides in human development, reflected in the lowered fertility rate, improved health and epidemiological outcomes, and progress in education, among others, are paving the way for its continued development and economic growth. Despite much progress, however, poverty and vulnerability remains a great challenge. In particular, persistent gaps across different populations exist often due to the labor market conditions experienced by marginalized workers (including unskilled laborers, females, youth, and migrants). In light of such dynamic changes in Bangladesh, the role of comprehensive Social Protection and Labor (SPL) policy to facilitate poor and vulnerable households to adequately respond to and manage various risks, is greater than ever. The recently endorsed National Social Security Strategy (NSSS) proceeds in this direction by adopting the lifecycle approach. This Social Protection and Labor Review report complements the NSSS with discussions on specific issues and policy recommendations. The report reviews the landscape of the sector, identifies key challenges to be overcome, and provides options for policy intervention. Overall, the review emphasizes the need for policy direction to shift from individual programs towards an overall strategy for households; from fragmented safety nets towards a comprehensive system; and from (ex-post) disaster reliefs towards (ex-ante) promotion of productive income generating activities. Therefore, the report greatly underscores the importance of strengthening labor market intervention and developing social insurance while addressing implementation challenges related to existing social assistance programs. In contrast to the multitude of various social assistance programs, Bangladesh currently lacks effective measures to promote labor market employment and productivity and adequate social insurance to hedge various risks. In the short term, the report suggests that policy efforts need to be made to introduce active labor market programs to provide greater employment opportunities, particularly for disadvantaged populations. Strategies to develop a pension system that can cover workers regardless of their type of employment are also needed. These measures will serve as building blocks for broader policies for more, better, and inclusive jobs, and a comprehensive social insurance system, which will contribute to the country’s goal of achieving middle income country status by 2021.